Focal facial dermal dysplasias type III: Two families with Setleis syndrome in China. Issue 10 (17th June 2022) - Cao, Qiaoyu; Zhang, Shuai; Wang, Jianbo; Wang, Yumeng; Pan, Chaolan; Wang, Xinyi; Zhao, Anqi; Chen, Xiao; Qin, Pingping; Zhang, Shoumin; Yao, Zhirong; Lv, Dong; et al.
Abstract: Focal facial dermal dysplasias type III (FFDD III), commonly known as Setleis syndrome (SS; Online Mendelian Inheritance in Man #227260), is a type of focal facial dermal dysplasia, characterized by bitemporal atrophic skin lesion. The homozygous mutations in the TWIST2 gene and copy number variants (CNV) at chromosome 1p36.22p36.21 were reported as the pathogenic mechanism. In this study, we collected DNA samples from a large Chinese family affected by FFDD and found no mutation of TWSIT2 . To determine the underlying genetic cause, we performed a multipoint parameter linkage analysis and haplotype analysis of the family 1 and mapped SS to a region Chr1:14.074–20.524cM (rs2401090–rs2294642). Copy number variant was identified by Sanger sequencing, which breakpoints were Chr1:11695972 and Chr1:11829858. The region contains eight genes, including FBXO2, FBXO44, FBXO6, MAD2L2, DRAXIN, AK125437, AGTRAP, and C1orf167 . There were no candidate gene mutations of the second family with SS. Our study further reduced the size of CNV resulting in SS (Chr1:11696993–11829858) and focused on eight genes.